Removal Of Oil From Aqueous Solution By Untreated Sugarcane Bagasse - Ahmad Samsuir, Asilah (2016)
Oily wastewater is one of the environmental concems nowadays. The seriousness of oil pollution problem comes in sync with the expansion of 011 exploration and production activities, as well as industrial growth around the world. The ability of sugarcane bagasse in removing oil in aqueous solution was investigated. Response Surface Methodology (RSM) was used in this study to optimize the oil removal in aqueous solution. The parameters observed in this study were concentration of synthetic oil wastewater, biosorbent dosage and contact time. Sugarcane bagasse showed excellent efﬁciency in removing oil with percentage removal up to 100% even at low condition of those parameters. The usage of sugarcane bagasse in removing the oil in water is proven and effective.